Eighteen‐Month‐Old Infants Correct Non‐Conforming Actions by Others. (3rd April 2019) - Schmidt, Marco F. H.; Rakoczy, Hannes; Tomasello, Michael
Abstract : At around their third birthday, children begin to enforce social norms on others impersonally, often using generic normative language, but little is known about the developmental building blocks of this abstract norm understanding. Here, we investigate whether even toddlers show signs of enforcing on others interpersonally how "we" do things. In an initial dyad, 18‐month‐old infants learnt a simple game‐like action from an adult. In two experiments, the adult either engaged infants in a normative interactive activity (stressing that this is the way "we" do it) or, as a non‐normative control, marked the same action as idiosyncratic, based on individual preference. In a test dyad, infants had the opportunity to spontaneously intervene when a puppet partner performed an alternative action. Infants intervened, corrected, and directed the puppet more in the normative than in the non‐normative conditions. These findings suggest that, during the second year of life, infants develop second‐personal normative expectations about their partner's behavior ("You should do X!") in social interactions, thus making an important step toward understanding the normative structure of human cultural activities. These simple normative expectations will later be scaled up to group‐minded and abstract social norms.